Current Status and Potential Therapeutic Strategies for Using Non-coding RNA to Treat Diabetic Cardiomyopathy - Rai, Amit K.; Lee, Brooke; Gomez, Ramesh; Rajendran, Deepu; Khan, Mahmood; Garikipati, Venkata Naga Srikanth (Frontiers in Physiology, 2021)
Diabetic cardiomyopathy (DMCM) is the leading cause of mortality and morbidity among diabetic patients. DMCM is characterized by an increase in oxidative stress with systemic inflammation that leads to cardiac fibrosis, ultimately causing diastolic and systolic dysfunction. Even though DMCM pathophysiology is well studied, the approach to limit this condition is not met with success. This highlights the need for more knowledge of underlying mechanisms and innovative therapies. In this regard, emerging evidence suggests a potential role of non-coding RNAs (ncRNAs), including micro-RNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs) as novel diagnostics, mechanisms, and therapeutics in the context of DMCM. However, our understanding of ncRNAs’ role in diabetic heart disease is still in its infancy. This review provides a comprehensive update on pre-clinical and clinical studies that might develop therapeutic strategies to limit/prevent DMCM.